Possible Technological Innovations for Industry 4.0 Practice in Furniture Industry of Bangladesh - Rayhan, Dewan Sabbir Ahammed; Ahmad, Farid (Review of Industrial Engineering Letters, 2021)
The Furniture Industry of Bangladesh has grown from the cotton industry in the early ’90s. It comprises 71034 firms of which 81 are medium-scale factories and 70953 are micro and small scale factories. Both local and global remarkable rapid growth of the furniture industry has made this sector a profitable investment sector. This giant export market is dominated by China and Malaysia because of their technological innovations, up-gradation, and rapid technology transfer mechanisms to meet the requirements of industry 4.0. To catch this big furniture export market, Bangladeshi furniture manufacturers need to be updated by innovations and technologies with industrial revolution 4.0 (IR 4.0). This study tries to find out some possible technological innovations for furniture manufacturers of Bangladesh for upgrading with industrial revolution 4.0 (IR 4.0), such as composite raw materials development, digital manufacturing, jointer machine, additive manufacturing technology, and 3D printing technology, etc. As technology transfer (TT) mechanism stimulates the innovation activities, this paper also shows a partially true modified technology transfer (MTT) model for small and medium enterprises (SMEs), start-ups, and large companies. Moreover, some existing technologies and pieces of machinery of Bangladeshi furniture manufacturers are illustrated with their applications.